ICT systems security and privacy protection : 34th IFIP TC 11 International Conference, SEC 2019, Lisbon, Portugal, June 25-27, 2019, proceedings /: 34th IFIP TC 11 International Conference, SEC 2019, Lisbon, Portugal, June 25-27, 2019, proceedings. ([2019]) - Unknown
No abstract available